2018
DOI: 10.1002/hup.2655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levocetirizine and diphenhydramine on regional glucose metabolic changes and hemodynamic responses in the human prefrontal cortex during cognitive tasks

Abstract: ObjectiveAntihistamines often have sedative side effects. This was the first study to measure regional cerebral glucose (energy) consumption and hemodynamic responses in young adults during cognitive tests after antihistamine administration.MethodsIn this double‐blind, placebo‐controlled, three‐way crossover study, 18 healthy young Japanese men received single doses of levocetirizine 5 mg and diphenhydramine 50 mg at intervals of at least six days. Subjective feeling, task performances, and brain activity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In Kikuchi et al, 2018, fNIRS signal is superimposed on standard MRI template images to compare the sedative effects of antihistamines in term of cerebral glucose metabolic changes measured by PET and hemodynamic response measured by fNIRS [17]. Therefore, if fNIRS signal could be view on the own subject image, we can view both information in one image of the same subject.…”
Section: Discussionmentioning
confidence: 99%
“…In Kikuchi et al, 2018, fNIRS signal is superimposed on standard MRI template images to compare the sedative effects of antihistamines in term of cerebral glucose metabolic changes measured by PET and hemodynamic response measured by fNIRS [17]. Therefore, if fNIRS signal could be view on the own subject image, we can view both information in one image of the same subject.…”
Section: Discussionmentioning
confidence: 99%
“…3. The details of this study are found in elsewhere [15]. Before the preparation for the NIRS examination, the subject was inserted with normal saline drip into the left antecubital vein.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…It is involving the injection of a radiotracer into human body where the tracer is a biological compound of interest labelled with a positron emitters isotope such as 11 C, 18 F and 15 O [11]. Specific tracers are chosen to illustrate the particular brain functions, for example, 18 F-2-deoxyglucose ( 18 FDG) is used to investigate cerebral glucose metabolism, whereas H2 15 O is used to examine cerebral blood flow [11].…”
Section: Introductionmentioning
confidence: 99%